Alopecia: Association with resistance to thyroid hormones - (:unkn) unknown (Walter de Gruyter GmbH, 2009)
Resistance to thyroid hormone (RTH) syndrome is caused by thyroid hormone β receptor (TRβ) mutations. Goiter, learning disabilities, psychological abnormalities, sinus tachycardia, hearing deficits, short stature, and growth delay are among the most common symptoms in patients with RTH. Alopecia areata (AA) is an autoimmune disease of the hair follicle, frequently associated with other autoimmune disorders. In some cases local alopecia of different genetic backgrounds could be misdiagnosed as AA. We describe here clinical, biochemical and genetic features of a family having RTH syndrome, caused by a novel TRβ mutation, coexistent with alopecia. Mutational analyses of the TRβ gene and the hairless gene (HR) in genomic DNA were performed. The index patient is a 9-4/12 year-old boy with RTH due to a novel heterozygous missense mutation of the TRβ gene (I353V), and diffuse, patchy alopecia without autoimmune thyroid disease. This mutation was also detected in his father and elder brother, who also have local alopecia. One of his paternal aunts and paternal grandmother have local alopecia and they have previously been operated for goiter. Although they refused any genetic analysis, the pre-operative medical report of the paternal aunt was compatible with RTH. A second paternal aunt has alopecia totalis universalis but has no RTH mutation in genomic DNA. Genomic DNA sequence of the HR gene of the family (index patient, two brothers, father, mother and second paternal aunt) was normal as well. Conclusion: We speculate that RTH due to a novel 1353V TRβ1 mutation could be causally related to different phenotypic expressions of alopecia in this family, either by a direct effect of unresponsiveness to T3 of the hair follicle or by the modulated action of the HR gene. © Freund Publishing House Ltd.
Keywords: Alopecia; Alopecia totalis universalis; Hairless gene; Resistance to thyroid hormone; Thyroid hormone receptor beta (TRβ) mutation